2012
DOI: 10.1186/1472-6920-12-13
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes towards medical students at Damascus University teaching hospitals

Abstract: BackgroundThe cooperation of patients and their consent to involve medical students in their care is vital to clinical education, but large numbers of students and lack of experience as well as loss of privacy may evoke negative attitudes of patients, which may sometimes adversely affect the clinical teaching environment. This study aimed to explore the attitudes of patients towards medical students at Damascus University hospitals, and to explore the determinants of those attitudes thus discussing possible im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 22 publications
13
49
0
Order By: Relevance
“…Although this finding is consistent with previously conducted studies,[23478] it emphasizes the need to prepare medical students for their first contact with patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although this finding is consistent with previously conducted studies,[23478] it emphasizes the need to prepare medical students for their first contact with patients.…”
Section: Discussionsupporting
confidence: 92%
“…[34] On the other hand, the negative attitude of patients in the obstetrics department may be explained by their concern for privacy. [791011] Marwan et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary health care training also places emphasis on individual autonomy and the necessity for consent before learners can be included in patient care. This may lead to occasions when patient preference and learner needs conflict . Studies evaluating patient attitudes towards medical students across a variety of specialties have demonstrated that, by and large, health care recipients are comfortable with the involvement of learners, although negative opinions regarding learners do exist.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating patient attitudes towards medical students across a variety of specialties have demonstrated that, by and large, health care recipients are comfortable with the involvement of learners, although negative opinions regarding learners do exist. In particular, concerns of privacy and the limited experience of students are not uncommon . This is important to keep in mind because, although many health care settings simultaneously serve as learning environments for students, consent to involving students in patient care should not be assumed.…”
Section: Introductionmentioning
confidence: 99%